Evaluation of serum protein electrophoresis in suspected cases of multiple myeloma - Karki, Shovana; Basnet, Alina; Simkhada, Ankita (Journal of Pathology of Nepal, 2025)
Background: Plasma cell neoplasm is a spectrum of diseases ranging from monoclonal gammopathy of unknown significance to plasma cell leukaemia. These plasma cells secrete immunoglobulin, which can be isotyped by immunoelectrophoresis or immunofixation. This study aimed to detect M protein in suspected cases of multiple myeloma and to identify the isotype of the M protein identified. Materials and Methods: Serum samples received in the Department of Pathology, Maharajgunj Medical Campus, Kathmandu, Nepal, from May 2022 to April 2024 were included in the study. Protein electrophoresis and isotyping were performed by automated capillary electrophoresis, Sebia Capillarys 2 Flex Piercing System. SPSS Vs 16 was used for statistical analysis. Results: Among the 1839 serum samples received, M-protein was seen in 94 cases (5.1%). Protein electrophoresis showed M spike in the gamma region in 62 cases (65.9%). In 33 cases (35.1%), where bone marrow diagnosis was available, multiple myeloma was seen in 23 cases (69.6%), lymphoplasmacytic lymphoma in eight cases (24.2%), and marginal zone lymphoma in two cases (6.2%). Forty-seven cases (50%) had immunotyping, which showed IgG kappa in 19 cases (40.4%), followed by IgA lambda. Elevated IgG kappa was associated with multiple myeloma, 83.3%, and Ig M kappa with lymphoplasmacytic lymphoma, 71.4%, p 0.001. Conclusions: IgG kappa is the most common immunoglobulin identified in multiple myeloma. In plasma cell neoplasm, the M spike is primarily IgG kappa located in the gamma region. However, when Ig M is observed in the beta region, other possibilities must also be considered.